ZOOMED IN, ZONED OUT: Academic Self-Reports on the Challenges and Benefits of Online Teaching in Higher Education - Gayathri Rajaraman; Rudi Klein; Puspha Sinnayah (Education Sciences, 2024)
Online teaching in higher education has become increasingly prevalent, especially in light of the COVID-19 pandemic. While teaching online offers many benefits, it also presents several challenges. Sharing one’s lived experiences as an educator is essential to improving one’s teaching skills and enhancing the learning outcomes for the students. Here, we present our personal and lived experiences as higher education teachers in the VU Block Model® First Year College at Victoria University. In our allied health science subjects, we have identified the key challenges in online teaching, such as technology and infrastructure, student engagement and interaction, adapting learning styles, assessment integrity, digital literacy, social-isolation-related mental health, and workload. The benefits included flexibility, innovative teaching tools, personalised learning and accessibility, and the continuity of teaching and learning despite the pandemic disruption. Overcoming these challenges requires careful planning, effective pedagogy, and ongoing support for both teachers and students. The benefits of online teaching can be maximised when its limitations are acknowledged and addressed appropriately via sharing teacher’s personal narratives as an effective mode of communication.